Archaeological Experiment on Reconstruction of the “Compound” Bow of the Sintashta Bronze Age Culture from the Stepnoe Cemetery - Ivan Semyan (EXARC Journal, 2021)
This article presents data from an international experimental study on the reconstruction of the “compound” bow of Sintashta culture of bronze age South Ural, Russia. The project is carried out by a collective of researchers from Greece and Russia as part of the grant program of the world association of experimental archaeology EXARC - “Twinning program”. The article reviews the global context of the design features of bows of the Neolithic-Bronze Age. The features and parts of the Sintashta “compound” bow were considered, and the role of long-range weapons in the life of Sintashta society was discussed. Using authentic technologies and materials, the authors of the article managed to make four versions of the bow reconstruction prior to obtaining the correct version.